Analisa Kelelahan Kerja pada Pekerja Bagian Gudang di PT Indomarco Prismatama Batam. - Silitonga, Ovin Chasvanis; Zetli, Sri (Computer Science and Industrial Engineering, 2020)
ABSTRACT Work fatigue is a problem that often occur at work area, this problem often ignored for continuity production of company. Uncontrolled work fatigue can caused a negative effect both physic and psychology for employee. In this study, the employee got workload about 35 kg/hour and overtime until 12 hour/day that caused the work fatigue. The aims of study to know a level category of work fatigue and factor of work fatigue what had the employee especially on warehouse of PT Indomarco Prismatama Batam. The method of the study used subjective self rating test that measure the level of subjective work fatigue toward the employee. The result of the study showed that the category of fatigue toward the employee of warehouse have a high level which is followed by a middle level. The result of Correlation Spearman test shows that working day (sig = 0,00), workload (sig = 0,00), the effect of work fatigue. The suggestion toward employee of warehouse conveys to do a job or workload based on physical ability and working capacity to take a short break. The leader of PT Indomarco Prismatama expects to increase mechanical equipment in loading and moving material activity even shifting working day correctly.